Інформаційно-психологічний вплив у розрізі безпеки здоров'я - Хворост, Христина Юріївна; Khvorost, Khrystyna Yu. (Південноукраїнський національний педагогічний університет імені К. Д. Ушинського, 2016)
У статті обґрунтовано взаємозалежність здоров'я особистості та інформаційно-психологічного впливу, що безпосередньо здатний змінити стан безпеки людини. Розглянуто основні види інформаційно-психологічного впливу на особистість. Сконструйовано модель інформаційно-психологічного впливу. Обгрунтовано взаємозв'язок інформації та здоров'я особистості, інформаційно-психологічний вплив та наслідки його дії на безпеку здоров'я людини у ході соціально-інформаційної взаємодії. Результати дослідження показали, що інформаційно-психологічний вплив є потужним чинником сучасного інформаційно-технічного суспільства, що має глибокий вплив на здоров'я людини та є на сьогоднішній день основоположним аспектом регулювання стану психічного, фізичного та соціального здоров'я індивіда та збереження здоров'я соціуму, нації, культури в цілому.

The article deals with the role of information and psychological impact on human’s organism and health, which is considered to be a powerful factor of modern information technology having strong influence on human health security. The study is aimed at investigating the dependence of information and psychological impact mechanisms and individual health, which directly can change state of human health security. The method of modelling has shown that a fundamen-tal aspect of controlling mental, physical and social health and health preservation at social, cultural and national levels is the ability to establish adequate behaviour while receiving the information. Depending on the particular kind of in-formation and psychological impact specificity, individual traits and previous information experience processing, a per-son can influence and regulate his/her health and strengthen his/ her own security. It has been determined that two main kinds of information and psychological impact are of the key importance in the formation of individual health security. These kinds of impact are based on the moral and semantic filter and unconscious perception of information. Among all stream of data an individual focuses only on its specific fragments. Way of thinking, worldview, values, spiritual, mate-rial interests influence the process of information enrichment, development of moral and semantic filter. At the same time, the enrichment of this filter involves national and ethical values, historical factors, education, religious and phi-losophical views, ideological propaganda, needs, mass media. A person makes specific decisions concerning the re-ceived information when analysing data absorbing it through the filter, which then are turned into actions and deeds. As a result, the level of adequate behaviour formation depends on some specific factors like degree of information and psychological attitude, decision making ability, typical behaviour, etc. In addition, it has been revealed that the specificity of human psyche influences his/her resistance to uncontrolled non-verbal information impact.
Information and psychological impact in terms of health security
Keywords: інформація; безпека здоров'я; інформаційно-психологічний вплив; загрози; здоров'я особистості; information; health security; information and psychological impact; threats; health identity